Wave Transmission Past A Submerged Semicircular Breakwater: A Numerical Approach - Loo, Kah Hou (Universiti Teknologi PETRONAS, 2018)
Breakwaters are coastal structures that act as protection for harbours and shorelines from coastal erosion due to the impact of waves. Semicircular breakwaters have been developed to improve the hydrodynamic performance of the structure. Gupta (2018) carried out physical modelling to investigate the hydrodynamic coefficients of an emerged and submerged semicircular breakwater subjected to regular wave conditions. The experimental results require validation by the numerical outputs. A series of numerical models using ANSYS-FLUENT were undertaken in this research study to evaluate wave transmission past a submerged semicircular breakwater. 20 test runs were chosen based on the experimental inputs given by Gupta (2018). The variables for this numerical simulation were wave period, wave height and water depth.